2011
DOI: 10.4049/jimmunol.1003279
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Role of Lipin-1 in Human Macrophages

Abstract: The lipins have been described as metabolic enzymes that regulate lipid biosynthesis and also signaling processes by controlling the cellular concentration of bioactive lipids, phosphatidic acid, and diacylgycerol. In the present work we have studied the subcellular localization and role of lipin-1 in human monocyte-derived macrophages. Human macrophages express lipin-1 isoforms α and β. A transfected lipin-1α–enhanced GFP construct associates with membranes of cellular organelles that can be stained with Nile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 74 publications
2
82
0
8
Order By: Relevance
“…However, TAG synthesis itself does not appear to be regulated by lipin-1, because depletion of this protein does not affect the rate of fatty acid incorporation into TAG (20). In this study, we have observed that TAG mass in lipin-2-depleted macrophages, either human or murine, is significantly decreased as compared with cells expressing normal lipin-2 levels, and this occurs under normal or fatty acid overload conditions.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…However, TAG synthesis itself does not appear to be regulated by lipin-1, because depletion of this protein does not affect the rate of fatty acid incorporation into TAG (20). In this study, we have observed that TAG mass in lipin-2-depleted macrophages, either human or murine, is significantly decreased as compared with cells expressing normal lipin-2 levels, and this occurs under normal or fatty acid overload conditions.…”
Section: Discussionsupporting
confidence: 52%
“…In previous work, we demonstrated that lipin-1 modulates size, amount, and TAG fatty acid composition of lipid droplets in human macrophages (20). However, TAG synthesis itself does not appear to be regulated by lipin-1, because depletion of this protein does not affect the rate of fatty acid incorporation into TAG (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies about LPINs involved lipid biosynthesis and its related roles in adipose tissue or, more recently, in macrophages (Valdearcos et al, 2011). Here, we have suggested a previously unknown function of amino acids derived from LPIN3 protein by identifying and characterizing a cell-penetrating peptide, which is located on its nuclear localization sequence.…”
Section: Discussionmentioning
confidence: 80%